Service Marketing Communication Training for Motorcycle Repair Shops in the Second Period of 2025 - Veny Ari Sejati (Journal of Communication, Sustainability, and Empowerment, 2025)
Today's youth are expected to be more productive in order to have a decent life and create job opportunities for others, so that society's prosperity increases. One way is to start a motorcycle repair shop for interested teenagers or those who already have motorcycle engine mechanical skills. Startup entrepreneurs need to have service service marketing communication knowledge so that their repair shops will grow and develop into medium to large-scale repair shops. Therefore, a service marketing communication training program for motorcycle repair shops will be held in November 2024 at the Suzuki Motor repair shop in Magetan city, branch of PT. ISG Surabaya, with participants being mechanics and apprentices. This research uses a descriptive qualitative technique, and data collection is done using the participant observation technique where the author is directly involved in the daily implementation of the training. Additionally, interviews are conducted when needed.  The purpose of this research is to explain how service marketing communication training is conducted for motorcycle repair shops. The training material covers service marketing communication, how to manage a repair shop, and is expected to create job opportunities in their respective areas. Participants practiced creating marketing plans, determining costs, creating repair shop promotions, and determining place and physical evidence. The reseacher hopes this article will be beneficial to other repair shop entrepreneurs by expanding their knowledge and providing ideas for developing their repair shops.